Pakistan Development Update, November 2017 : Managing Risks for Sustained Growth - World Bank (World Bank, Islamabad, 2017)
The objective of this report is to apprise the Government of Pakistan, think-tanks and researchers, the public and The World Bank's senior management of the state of Pakistan's economy, outlook, structural reforms and development challenges. The report begins with a chapter on economic developments, with sections on growth, fiscal policy, public debt, the external sector, and inflation and monetary developments. The second chapter provides a medium-term macroeconomic outlook and describes upcoming challenges, and structural reform needs. The third chapter focuses on progress against social indicators. The final chapter addresses entrepreneurship in Pakistan from the perspectives of jobs, enabling new startup businesses, women's entrepreneurship and export competitiveness.